Prevalence of overweight and obesity among school children of Bhaktapur and Kathmandu (Journal of Kathmandu Medical College, 2019)
Background: World Health Organization defines childhood obesity as “one of the most serious public health challenges”. Low income countries like Nepal experience a burden of infectious diseases as well as rising incidence of noncommunicable diseases frequently associated with obesity. There is paucity of information on childhood obesity in Nepal.Objectives: This study aims to determine the prevalence of childhood obesity and overweight in school going children and find its association with blood pressure.Methodology: A school based cross-sectional analytical study was conducted on 509 children aged between 10-16 years, studying in grade 5-10 of private schools in Kathmandu and Bhaktapur. Simple random sampling technique was used for data collection. Anthropometric measurements and blood pressure were taken using standard protocol. Obesity was assessed using Body Mass Index criteria.Results: The overall prevalence of obesity and overweight in children were found to be 1.6% and 6.1% respectively. This study also showed that prevalence of obesity in children from Kathmandu is comparatively more, which was statistically significant (p